Single-shot quantitative phase microscopy with the transport-of-intensity equation - Zuo, Chao (2013)
We present a single-shot experimental configuration for quantitative phase microscopy recovery based on the transportof- intensity equation (TIE). The system can simultaneously capture two laterally separated images with different amounts of defocus using only one digital camera. The defocus distance can be adjusted by varying the free space propagation transfer function on a phase only spatial light modulator. The intensity derivative along optics axis can thus be estimated optimally. In contrast to the state of the art techniques, this configuration requires no mechanical moving parts. Furthermore its single-shot property allows potential application for measuring fast moving objects or dynamic processes. Validation experiments are presented.